2019
DOI: 10.3390/polym11060933
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Epoxidized Canola Oil (eCO) and Cellulose Nanocrystals (CNCs) on the Mechanical and Thermal Properties of Polyhydroxybutyrate (PHB)—Poly(lactic acid) (PLA) Blends

Abstract: Two major obstacles to utilizing polyhydroxybutyrate (PHB)—a biodegradable and biocompatible polymer—in commercial applications are its low tensile yield strength (<10 MPa) and elongation at break (~5%). In this work, we investigated the modification of the mechanical properties of PHB through the use of a variety of bio-derived additives. Poly(lactic acid) (PLA) and sugarcane-sourced cellulose nanocrystals (CNCs) were proposed as mechanical reinforcing elements, and epoxidized canola oil (eCO) was utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
5
37
0
1
Order By: Relevance
“…In the low frequency region, a homopolymer typically presents a decline of 2, whereas for ABS, which is a copolymer, the drop is smaller than 2. 20 In addition, the CNC 150 /ABS nanocomposites displayed viscoelastic response similar to pure ABS, therefore, no significant structural modification is apparent.
Figure 4.Storage modulus (G′) versus loss modulus (G″) for pure ABS and the nanocomposites.
…”
Section: Resultsmentioning
confidence: 98%
“…In the low frequency region, a homopolymer typically presents a decline of 2, whereas for ABS, which is a copolymer, the drop is smaller than 2. 20 In addition, the CNC 150 /ABS nanocomposites displayed viscoelastic response similar to pure ABS, therefore, no significant structural modification is apparent.
Figure 4.Storage modulus (G′) versus loss modulus (G″) for pure ABS and the nanocomposites.
…”
Section: Resultsmentioning
confidence: 98%
“…The GPC method is described in our previous work. [51] Large scale graphite flakes were purchased from Alfa Aesar Inc. Sulfuric acid (98%), hydrogen peroxide (30%), phosphoric acid (98%), hydrochloric acid (37%), and potassium permanganate particles were purchased from Fisher Scientific, Canada and used as received. Glacial acetic acid (99%), l-ascorbic acid (l-A.A) were provided from Sigma-Aldrich, Canada, and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that after seven days of aging, the crystallinity of the PHB sample increased from the initial 20.5% to 28.2%. This change in the material could impact its overall mechanical properties, since the degree of crystallinity increases, it will influence the impact resistance, the young's modulus and elongation at break [92,93]. In another study by Srubar et al, samples of PHB were isothermally conditioned at 15 • C in a desiccated environment for 168 days in order to investigate the effects of aging at storage temperatures slightly above the Tg of the material.…”
Section: Aging Of Phb Materialsmentioning
confidence: 99%